Life on the battlefield: Valproic acid for combat applications. Issue 2 (August 2020) - Russo, Rachel; Kemp, Michael; Bhatti, Umar F.; Pai, Manjunath; Wakam, Glenn; Biesterveld, Ben; Alam, Hasan B.
Abstract : ABSTRACT: The leading causes of death in military conflicts continue to be hemorrhagic shock (HS) and traumatic brain injury (TBI). Most of the mortality is a result of patients not surviving long enough to obtain surgical care. As a result, there is a significant unmet need for a therapy that stimulates a "prosurvival phenotype" that counteracts the cellular pathophysiology of HS and TBI to prolong survival. Valproic acid (VPA), a well-established antiepileptic therapy for more than 50 years, has shown potential as one such prosurvival therapy. This review details how VPA's role as a nonselective histone deacetylase inhibitor induces cellular changes that promote survival and decrease cellular pathways that lead to cell death. The review comprehensively covers more than two decades worth of studies ranging from preclinical (mice, swine) to recent human clinical trials of the use of VPA in HS and TBI. Furthermore, it details the different mechanisms in which VPA alters gene expression, induces cytoprotective changes, attenuates platelet dysfunction, provides neuroprotection, and enhances survival in HS and TBI. Valproic acid shows real promise as a therapy that can induce the prosurvival phenotype in those injured during military conflict.